Increasing the Satisfaction and Loyalty of Lion Parcel’s Customers in Indonesia - Angelica, Irene; Astria, Nathania; Sitorus, Marthaleina Ruminda; Ghafar, Abdul (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2023)
This study aims to examine the effect of brand image, social media and price perceptions on customer satisfaction and loyalty at Lion Parcel in Indonesia. This sample is 179 respondents who use Lion Parcel expedition services. Data analysis using Structural Equation Modeling-Partial Least Square (SEM-PLS 4.0). The result of this study show that brand image has a positive and significant effect on customer satisfaction. Social media has a positive and significant effect on customer satisfaction. Price perception has a positive and significant effect on customer satisfaction. And customer satisfaction has a positive and significant effect on customer loyalty. The result of this artikel can be basis for Lion Parcel to improve their marketing skill by considering social media users and price perceptions that are aligned with their benefit.